The eroticization of bikutsi: reclaiming female space through popular music and media. - Rathnaw, Dennis M. (International Library of African Music, 2010)
THis work examines the development of bikutsi from traditional song form to media, moral and cultural issue - a site of contestation between local media officials and an increasingly more internationally influenced and liberalized media. I analyze the experience of bikutsi as mediated by politics and external and internal views and consumption. As the Cameroonian media undergoes a process of democratization highly influenced by foreign media, local musicians and video artists become actors in a conflicted and uncertain environment. On the one hand are issues of nation-building and cultural development in the face of dominant foreign media, and on the other, the multitude of images, sounds and forms of popular culture people attach themselves to in their daily imaginings.
Keywords: African Music